Collagenous sprue diagnosed by double balloon endoscopy. Issue 1 (17th December 2012) - Yamamoto, Yu; Yamada, Takeshi; Akutsu, Daisuke; Sugaya, Akinori; Murashita, Tetsuya; Matsuda, Kenji; Yamamoto, Yoshiyuki; Kusakabe, Ryoko; Kaneko, Tsuyoshi; Suzuki, Hideo; Hyodo, Ichinosuke; Sato, Taiki; et al.
<x xml:space="preserve">Abstract</x> Double balloon endoscopy (DBE) is useful for diagnosing many intestinal diseases and for endoscopic procedures. We report a case of chronic diarrhea in a 58‐year‐old Japanese man. He was initially suspected to have malabsorption syndrome. DBE showed reduction of folds, scalloping, mucosal nodularity and granularity. Pathological examinations of biopsies from the jejunum showed severe villous atrophy with subepithelial collagen bands. These findings led to the final diagnosis of collagenous sprue (CS). With1 month of total parenteral nutrition followed by a low‐gluten diet, his symptoms gradually improved. CS has never been reported before in Japan. DBE is useful for making a diagnosis of CS, and may be considered for patients who are suffering from diarrhea of unknown cause.